2012
DOI: 10.1017/jfm.2012.69
|View full text |Cite
|
Sign up to set email alerts
|

Boundary layers and wind in cylindrical Rayleigh–Bénard cells

Abstract: We analyse the wind and boundary layer properties of turbulent Rayleigh–Bénard convection in a cylindrical container with aspect ratio one for Prandtl number $\mathit{Pr}= 0. 786$ and Rayleigh numbers ($\mathit{Ra}$) up to $1{0}^{9} $ by means of highly resolved direct numerical simulations. We identify time periods in which the orientation of the large-scale circulation (LSC) is nearly constant in order to perform a statistical analysis of the LSC. The analysis is then reduced to two dimensions by considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

52
132
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(190 citation statements)
references
References 45 publications
52
132
4
1
Order By: Relevance
“…The phase shift φ LSC characterizes the mean orientation of the LSC over a finite time interval. As stated above, all DNS [77,112,80] showed that this orientation can fluctuate strongly. Wagner et al [112] provided therefore a comparison of five different functions to determine finite-time interval average of φ LSC which were for example based on the local heat flux J c + J d or the azimuthal vorticity component and found that the heat flux criterion works best.…”
Section: Spatial Structure Of Large-scale Circulationsupporting
confidence: 60%
See 4 more Smart Citations
“…The phase shift φ LSC characterizes the mean orientation of the LSC over a finite time interval. As stated above, all DNS [77,112,80] showed that this orientation can fluctuate strongly. Wagner et al [112] provided therefore a comparison of five different functions to determine finite-time interval average of φ LSC which were for example based on the local heat flux J c + J d or the azimuthal vorticity component and found that the heat flux criterion works best.…”
Section: Spatial Structure Of Large-scale Circulationsupporting
confidence: 60%
“…This permanent change of the mean direction of the LSC is accompanied by a irregular temporal variation of its mean velocity magnitude. This is also the outcome of very recent high-resolution DNS by Wagner et al [112] and Shi et al [80] in which access to the full three-dimensional velocity field is given. These oscillations have been also measured earlier in the BOI [113].…”
Section: Spatial Structure Of Large-scale Circulationmentioning
confidence: 55%
See 3 more Smart Citations